The relationship of respiratory symptoms and bronchial responsiveness in competitive swimmers - Stensrud, T.; Stadelmann, K.; Carlsen, K.-H. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The prevalence of exercise induced asthma and bronchial hyperresponsiveness (BHR) is reported high among elite endurance athletes. Of the summer sports, swimmers show a high incidence of BHR and respiratory symptoms. From the winter Olympic Games 2002 and later the international Olympic Committee-Medical Commission (IOC-MC) required objective measurements of BHR or reversibility to bronchodilators to obtain approval for the use of 2-gonists in sports. The aims of the study were therefore to evaluate the relationship between respiratory symptoms in young elite swimmers and two different tests of BHR; Eucapnic voluntary hyperventilation (EVH) and the dose of inhaled methacholine causing 20% decrease in FEV1 (PD20 methacholine). Secondly we aimed to define the repeatability of the EVH test. METHODS: 15 male and 9 female adolescent elite swimmers, 15 to 25 years old, performed one measurement of PD20 methacholine and two EVH tests in randomised order. Dry air containing 5% CO2 was inhaled with a target ventilation of .85% MVV (minimum 65%) for 6 min. PD20 methacholine . 2 ƒÊmol and EVH . 10% decrease in FEV1 were considered positive according to the limits given by IOC-MC. The athletes reported their respiratory symptoms and medication use in the modified AQUA2008 questionnaire. RESULTS: Twenty swimmers (83%) reported respiratory symptoms, 15 of these (75%) had a positive provocation test. Fourteen (58%) of the 24 swimmers had at least one positive test result to either one EVH test or to PD20 methacholine. The sensitivity for PD20 methacholine . 2 ƒÊmol in relation to respiratory symptoms was 50% versus 60% and 47.37% for the two EVH tests, respectiveley and 75% for PD20 methacholine . 4 ƒÊmol. Bland-Altman plot of the two EVH tests showed a consistent distribution with only one subject outside the limits of agreement CI (-5.5, 6.8). DISCUSSION: The prevalences of BHR and respiratory symptoms among adolescent elite swimmers are very high. PD20 methacholine . 2 ƒÊmol and EVH . 10% agree but PD20 methacholine . 4 ƒÊmol shows the best sensitivity in relation to respiratory symptoms. This may infer that the symptoms occurring in swimmers may to some extent be unspecific and not always related to BHR, alternatively that the requirements set up by IOC-MC may be too strict. The EVH test has a high repeatability, but is very expensive and uncomfortable to perform.